Walter Banjamin e a Melancolia - Dias, Luís Francisco Fianco (Universidade do Vale do Rio do Sinos, 2004)
We shall see here the melancholia into a specified cultural movement, the Baroque. But we must remember that this kind of delimitation, even if it is associate to a special time definition, has not exclusive relation to the history, but allows to see the Baroque as an idea, and points to the baroque elements and representations out of these specific time limits. Our own time, in this way, can be saw as a baroque time, and that makes the justification of this subject into this dissertation and to the try of understanding the modern subjectivity. With the Baroque starts a way to the thinking that is still ours, divided between the Christian and the Hellenic references, where, through the dimension of guilt and sadness, we have personified our fragility. Into us there is the allegory and the melancholia, this one to say that the world has no meaning and that another to say that just trough her we could to have some kind of access to the things. The baroque man is made of a medley from the Middle Ages and the Reb
Keywords: barroco.; filosofia; melancolia; Walter Benjamin; baroque; melancholia; philosophy; Walter Benjamin; Ciências Humanas